Correlation of placental histomorphology with doppler velocimetry in preeclampsia and IUGR and their perinatal outcome - Solipuram, Divya; Vasudeva, Akhila; Adiga, Prashanth; Das, Ashwin; D’ Souza, Antony Sylvan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Though numerous placental ischemic changes are described in relation to placental insufficiency, universally accepted criteria are unavailable till date leading to under or over reporting. Present study is an attempt to define standardized grading system for placental dysmorphology and correlate it with Doppler changes. The objective was to study placental histomorphology in preeclampsia and IUGR (Intrauterine Growth Restriction), to correlate the placental histomorphology with multivessel Doppler findings and their perinatal outcome in preeclampsia and IUGR. Methods: Prospective study was done over 2 years, 64 antenatal women with preeclampsia and/or IUGR were recruited, their multivessel Doppler measurements were recorded and placental histomorphological changes were studied post-delivery which were graded as either low or high grade placentas considering degree and number of ischemic changes observed. Results: Out of 64 cases, 33 (51.5%) cases had low grade changes and 31 (48.5%) had high grade changes. Out of 33 patients with low grade placentas 24 (73%) had normal Doppler, 20 (65%) out of 31 high grade placenta had abnormal Doppler. Placental histomorphology correlated well with Doppler abnormality (Coefficient of Kappa test). Syncytial knots>50%, presence of hypermature villi, infarcts, fibrin deposits were significantly associated with abnormal Doppler. High grade placenta group had significantly poor perinatal outcome (Chi square test). Conclusions: We formulated a grading system of placental dysmorphology in preeclampsia and IUGR which correlated well with clinical Doppler abnormality and perinatal outcome. Further studies are warranted to develop preventive strategies aimed at specific high grade placental changes seen in pregnancies with abnormal Doppler and develop strategies to improve perinatal outcome.